Prevention & Management of Herpes Zoster- an Update (Bangladesh Medical Journal, 2014)
Herpes zoster (commonly referred to as "shingles") results .from reactivation of the varicella-zoster virus infection, or chickenpox. Were as varicella is generally a disease of childhood, herpes zoster becomes more common with increasing age Factors that decrease immune function, such as human immunodeficiency virus infection, chemotherapv, malignancies and chronic corticosteroid use, may also increase the risk of developing herpes zoster. Reactivation of latent varicella-zoster virus from dorsal root ganglia is responsible.for lhe classic dermatomal rash and pain that occur with herpes zoster. Burning pain typically precedes the rash by several days and can persist for several months after the rash resolves. With post herpetic neuralgia, a complication of herpes zoster, pain may persist well after resolution of the rash and can be highly debilitating. Although the diagnosis of the conditions is generally straightforward, treatment can be frustrating for the patient and physician. Approaches to management include treatment of the herpes zoster infection and associated pain, prevention of post herpetic neuralgia, and control of the neuropathic pain until the condition resolves. Herpes zoster is contagious to those who have not had varicella or have not received the varicella vaccine. The role of the varicella vaccine in preventing herpes zoster is uncertain, but is being studied. The management of herpes zoster is challenging because many patients develop troublesome complication. So, appropriate management o/'herpes zoster is very important to avoid complication. On the other hand prevention is better than cure. Immunization with varicella zoster virus vaccine may boost humoral and cell mediated and decrease the incidence of zoster in population. So effectiveness of a vaccination program need to be evaluated. immunity DOI: http://dx.doi.org/10.3329/bmj.v41i3.18961 Bangladesh Medical Journal 2012 Vol.41(3): 53-56